Basal Stress Fluctuation: Reply to Comment by Cagnoli on "Slope‐Break Collisions: Comment on 'Insight Into Granular Flow Dynamics Relying on Basal Stress Measurements: From Experimental Flume Tests' by K. Li et al.". Issue 2 (30th January 2023) - Li, Kun; Wang, Yufeng; Cheng, Qiangong; Lin, Qiwen; Wu, Yue; Long, Yanmei
Abstract: In the comment, Cagnoli (2022, https://doi.org/10.1029/2022JB024799 ) disagrees with our experimental conclusion that the enhanced particle agitation related to the high magnitude basal fluctuating stresses contributes to the granular flow mobility. Instead, he argues that the slope‐break model used in our experiments prevents the granular flows from being as mobile as they could be. In this reply, we restate our viewpoints by further clarifying the experimental variables and evaluating the effects of the additional phenomena raised in our experiments. By considering the granular flow velocities before the slope‐break, a linear correlation between the depth‐average velocity and equivalent friction coefficient is established, indicating that an increasing flow mobility with decreasing fractal dimension D has already been initiated before the slope‐break. Thus, the slope‐break collision has no significant effect on the general trend of the flow mobility versus grain size and the positive correlation between stress fluctuation and granular flow mobility is still valid. Plain Language Summary: At present, the high mobility of rock avalanches is still an unsolved mystery. Field observations of rock avalanche deposits, as well as the landquakes generated during rock avalanche propagations reveal that a series of physical processes are involved in rock avalanches, some of which should contribute to their high mobility. In our experiments (Li et al., 2022, https://doi.org/10.1029/2021jb022905 ), a plausible physical process related to rock avalanches was found, that is, the high magnitude fluctuating stresses generated by the interaction between the granular flow and subsurface could contribute to the mobility. However, this finding is questioned by Cagnoli (2022, https://doi.org/10.1029/2022JB024799 ) because he regards that the slope‐break model used in our study interfered with the reliability of the experimental results. Through further investigation and analysis of the experimental results, it is shown that the granular flow already exhibited a trend of greater mobility with a higher coarse particle content before the slope‐break. This means that the general trends of our experimental results were not changed by the slope‐break collisions and the physical process we found is still justified. Key Points: The enhanced mobility of the granular flow with increasing grain size is initiated before the slope‐break collision The generation of high‐magnitude fluctuating stress is the essential physical process promoting granular flow mobility in our study The discrepancy between experiments and simulations is attributed to the idealized physics of discrete element method